Transforming Ecotourism in Lampageu Village: an Asset-Based Approach for Sustainable Development - Amalia, Rizki; Pribadi, Jeliteng; Nabilah, Nabilah; Natasya, Dhea Diban; Faisal, Zarfa Dzi Izzati; Falah, Qushayyi; Hidayat , Teuku Arief; Fairuzabadi, Haura (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to develop a masterplan for ecotourism in Desa Lampageu using the Asset-Based Community Development (ABCD) approach. The research explores how local assets—both natural and cultural—can be mobilized for sustainable development. A qualitative descriptive methodology was employed, involving Focus Group Discussions (FGD), field observations, and interviews with community members, local leaders, and stakeholders. Data collection spanned three months and focused on identifying assets, creating a digital tourism map, and drafting a comprehensive masterplan integrated with the village budget. Results indicate that the ABCD approach fosters community participation and ownership, leading to practical outcomes such as new facilities and enhanced tourism visibility. This model offers replicable strategies for other villages aiming to achieve sustainable ecotourism.